2018
DOI: 10.1101/gr.233940.117
|View full text |Cite
|
Sign up to set email alerts
|

Selective maternal seeding and environment shape the human gut microbiome

Abstract: Vertical transmission of bacteria from mother to infant at birth is postulated to initiate a life-long host-microbe symbiosis, playing an important role in early infant development. However, only the tracking of strictly defined unique microbial strains can clarify where the intestinal bacteria come from, how long the initial colonizers persist, and whether colonization by other strains from the environment can replace existing ones. Using rare single nucleotide variants in fecal metagenomes of infants and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
300
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(322 citation statements)
references
References 36 publications
18
300
1
3
Order By: Relevance
“…Earlier studies indicated that the cage rearing effect may be caused by differences in early life gut microbial colonization process, including exposure to the maternal microbiome (e.g. breast-milk feeding and ingest the soft faeces of dams) and indigenous environment microbiome (Hufeldt, et al, 2010;Rogers, et al, 2014;Ericsson, et al, 2015;Yang, et al, 2017;Korpela, et al, 2018;Martinez, et al, 2018). Previous studies investigated the role of sex in adult animals' gut microbiota suggested that the significant difference of gut microbial composition between sexes was caused by sex hormones (Org, et al, 2016;Miyoshi, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies indicated that the cage rearing effect may be caused by differences in early life gut microbial colonization process, including exposure to the maternal microbiome (e.g. breast-milk feeding and ingest the soft faeces of dams) and indigenous environment microbiome (Hufeldt, et al, 2010;Rogers, et al, 2014;Ericsson, et al, 2015;Yang, et al, 2017;Korpela, et al, 2018;Martinez, et al, 2018). Previous studies investigated the role of sex in adult animals' gut microbiota suggested that the significant difference of gut microbial composition between sexes was caused by sex hormones (Org, et al, 2016;Miyoshi, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although we are unaware of any research suggesting that infants can counteract these measures, competitive exclusion (i.e., microbial competition for available niches and resources) can, in theory, also be driven by offspring gut motility and the biochemical makeup of the mucosal lining of the offspring gut . Further, offspring intestinal immune responses to maternal microbes can result in the selective seeding of certain maternal microbial strains over others . Thus, despite the magnitude of maternal microbiota and oligosaccharide transmission, offspring physiology ultimately shapes the maternal microbes that successfully colonize and proliferate within the infant gut.…”
Section: Proximate Mechanisms Of Developmental Plasticitymentioning
confidence: 99%
“…153,154 Further, offspring intestinal immune responses to maternal microbes can result in the selective seeding of certain maternal microbial strains over others. 155,156 Thus, despite the magnitude of maternal microbiota and oligosaccharide transmission, offspring physiology ultimately shapes the maternal microbes that successfully colonize and proliferate within the infant gut. Whether microbial strains might have similar mechanisms to counter offspring or maternal interests is fodder for future studies.…”
Section: Gut Microbiomementioning
confidence: 99%
“…These microbes have important roles in a variety of processes benefiting their host, ranging from nutrient metabolism to immunity (Albenberg & Wu, ; Chung et al, ; Dimmitt et al, ; Douglas, ; Jašarević, Rodgers, & Bale, ; Michalkova, Benoit, Weiss, Attardo, & Aksoy, ; Pais, Lohs, Wu, Wang, & Aksoy, ; Snyder & Rio, ; Wang, Weiss, & Aksoy, ; Weiss, Wang, & Aksoy, ). For most animals, their microbial community is established over development through interactions with the environment, through diet, as well as interactions with other organisms (Abdul Rahman et al, ; Blaser & Dominguez‐Bello, ; Carrasco et al, ; da Costa & Poulsen, ; Estes et al, ; Funkhouser & Bordenstein, ; Gilbert, ; Korpela et al, ; Kostic et al, ; Morse et al, ; Mueller, Bakacs, Combellick, Grigoryan, & Dominguez‐Bello, ; Perez‐Muñoz, Arrieta, Ramer‐Tait, & Walter, ; Schwab, Riggs, Newton, & Moczek, ; Shukla, Vogel, Heckel, Vilcinskas, & Kaltenpoth, ; Torrazza & Neu, ; Wang & Rozen, ). Of interest is the role that parent–offspring interactions play in the microbial acquisition during early development, specifically from mother to her offspring (Adair & Douglas, ; Dimmitt et al, ; Duranti et al, ; Fox & Eichelberger, ; Funkhouser & Bordenstein, ; Gilbert, ; Jašarević, Rodgers, et al, ; Korpela et al, ; Kostic et al, ; Perez‐Muñoz et al, ; Schwab et al, ; Torrazza & Neu, ; Wade, ; Walker, Clemente, Peter, & Loos, ).…”
Section: Introductionmentioning
confidence: 99%
“…These prolonged interactions provide means for multiple routes of vertical transmission of microbes from mother to her progeny (Funkhouser & Bordenstein, ; Ma et al, ; Mueller et al, ). In humans, while placental transmission of microbes is debated (Aagaard et al, ; Blaser & Dominguez‐Bello, ; Fardini, Chung, Dumm, Joshi, & Han, ; Perez‐Muñoz et al, ; Walker et al, ), mother to newborn transfer can occur during passage through the birth canal, breast feeding, and throughout early postnatal development (Ballard & Morrow, ; Dahlen, Downe, Kennedy, & Foureur, ; Duranti et al, ; Funkhouser & Bordenstein, ; Jašarević, Howerton, Howard, & Bale, ; Jašarević, Rodgers, et al, ; Korpela et al, ; Ma et al, ; Mueller et al, ). Other live‐bearing animals and their symbionts have evolved to utilize the extended gestation as a time to inoculate progeny with bacteria (Denlinger & Ma, ; Funkhouser & Bordenstein, ; Ma et al, ; Morse et al, ; Mueller et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%